Impact of microwave irradiation pretreatment on preservative retention and durability of outdoor-exposed Norway spruce - Ganguly, Sauradipta; Hom, Sanjeet Kumar; Sethy, Anil Kumar; Dan, Sanmitra; Debnath, Biswajit; Sharma, Varun; Tripathi, Sadhna; Kržišnik, Davor; Petrič, Marko (Elsevier, 2025)
Norway spruce (Picea abies L. Karst.) is a commercially valuable species, but has low permeability and susceptibility to decay, which requires an effective preservative treatment. In this study, the effect of microwave (MW) pretreatment on preservative retention and durability of wood during 30 months of outdoor exposure was investigated. MW-treated specimens showed a significant increase in preservative retention of borax-boric acid (BBA), with MW 36 treated specimens showing a retention of 40.79 kg/m3 compared to 7.90 kg/m3 for untreated controls. Durability assessment revealed that the MW treated specimens remained decay-free at higher energy levels (MW 28, MW 32, MW 36), whereas the untreated controls reached decay ratings of 3 in open conditions and 2 in shaded environments. Structural and chemical changes, including increased permeability, lignin content and crystallinity might have contributed to the increased resistance of MW-treated wood to fungal decay. The study also highlights the influence of climatic factors on the progression of decay, with MW pretreatment resulting in significant improvement in resistance to moisture-induced degradation. While lower MW energy levels (MW 20, MW 24) showed slight fungal growth, higher energy levels provided sustained protection, establishing the effectiveness of MW pretreatment as a promising technique to augment preservative retention and improve the in-service durability of wood. Future research should therefore investigate the mechanical effects, economic feasibility, and long-term performance of different commercial species in the field under different climatic conditions. The present study demonstrates that microwave pretreatment synergistically enhances the efficacy of BBA, which is a waterborne leachable but relatively safe wood preservative, potentially diminishing exclusive reliance on traditional toxic chemical preservatives to improve wood durability.
Keywords: wood modification; outdoor durability; MW pretreatment; sustainable wood preservation; climate resilient wood